Barium Appendicitis 6 Weeks After Upper Gastrointestinal Imaging - Shen, Gang; Sun, Kang; Fan, Zhe (Frontiers in Pediatrics, 2020)
Barium sulfate is widely used for gastroenterology imaging. Retention of barium in the appendix, where it acts as an appendicolith, thereby leading to obstruction and inflammation. Barium-associated appendicitis is a very rare complication of upper gastrointestinal imaging (UGI), especially in children. We present a case involving an 8-year-old girl who was diagnosed with acute appendicitis due to a barolith and required a laparoscopic appendectomy 6 weeks after UGI. After UGI, patients should be informed regarding possible retention of barium in the appendix, which can cause acute appendicitis. Then, a laparoscopic appendectomy was performed successfully. We should be cautious of this potential risk to prevent complications with early intervention in children.